Sex-differences in the longitudinal recovery of neuromuscular function in COVID-19 associated acute respiratory distress syndrome survivors - Lulic-Kuryllo, Tea; Benedini, Marco; Cogliati, Marta; Cudicio, Alessandro; Guarneri, Bruno; Gazzina, Stefano; Piva, Simone; Latronico, Nicola; Orizio, Claudio; Negro, Francesco (Frontiers in Medicine, 2023)
Introduction: Patients admitted to the intensive care unit (ICU) following severe acute respiratory syndrome 2 (SARS-CoV-2) infection may have muscle weakness up to one year or more following ICU discharge. However, females show greater muscle weakness than males, indicating greater neuromuscular impairment. The objective of this work was to assess sex differences in longitudinal physical functioning following ICU discharge for SARS-CoV-2 infection. Methods: We performed longitudinal assessment of physical functioning in two groups (fourteen participants (7 males, 7 females) in the 3-to-6 month and twenty-eight participants (14 males, 14 females) in the 6-to-12 month group) following ICU discharge and assessed differences between the sexes. We examined self-reported fatigue, physical functioning, compound muscle action potential (CMAP) amplitude, maximal strength, and the neural drive to the tibialis anterior muscle. Results: We found no sex differences in the assessed parameters in the 3-to-6-month follow-up, indicating significant weakness in both sexes. Sex differences emerged instead in the 6-to-12-month follow-up. Specifically, females exhibited greater impairments in physical functioning, including lower strength, walking lower distances, and high neural input even one year following ICU-discharge. Discussion: Females infected by SARS-CoV-2 display significant impairments in functional recovery up to 1 year following ICU discharge. The effects of sex should be considered in post-COVID neurorehabilitation.